Hubungan Kecemasan Kesehatan dengan Ketakutan terhadap COVID-19 pada Remaja Akhir di Jakarta - Anggie Harmalia Permata; Lenny Kendhawati; Marisa Fransiska Moeliono (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The pandemic situation has an impact, namely health anxiety and fear of COVID-19 which is felt in the community, one of which is adolescents. Negative emotions will have an effect on suppressing the immune response thereby reducing immunity (Kemeny, 2007; Seiler et al., 2020). This will certainly worsen the situation of the COVID-19 pandemic. Most cases of COVID-19 in Indonesia occur in Jakarta Province, so this study looks at the health crisis and fear of COVID-19 in 300 late adolescents in Jakarta and looks at the relationship between the two variables. This study uses a clustered on stratified sampling technique. Data collection for this study was carried out 9 months after it was decided that COVID-19 was a global pandemic. The method used in this study is a correlational technique. The results of this study found that late adolescents in Jakarta tend to have low health anxiety, namely 70.3% of participants (n = 211), but different from the high fear of COVID-19, which is 74% of participants (n = 222). The results of this study obtained data that health anxiety has a positive correlation with fear of COVID-19 (r = 0.225, p-value = 0.000). Based on the results of the study, it can be concluded that health anxiety in late adolescents in Jakarta has a weak relationship with fear of COVID-19.